Mental health in ultra-neoliberal times - Cavalcante, Lidiany de Lima; Bellini, Maria Isabel Barros (Argumentum, 2023)
The process of worsening barbarism, permeated by conservatism, reactionism and facets of discrimination, has exposed not only how violence and hunger have intensified, but also amplified previously silent platforms related to psychological illness. The article discusses mental health in ultra-neoliberal times, which increasingly emerged with the rise of the extreme right in Brazil. Through theoretical reflection, with the use of secondary data, the study reveals a scene of necropolitics, potentiated daily in the mental health arena, and in its repercussions on society, in the face of the most voracious form capitalism.